Driving startup growth: A comprehensive review of the AIDA model's impact on marketing communications - RA Loretta Kartikasari; Irma Setyawati; Rahayu Lestari (Indonesian Journal of Business, Accounting and Management, 2026)
Purpose- This paper aims to conduct a comprehensive review of the AIDA (Attention, Interest, Desire, Action) model and its impact on marketing communications within the startup ecosystem. The study specifically explores how startups can leverage the AIDA framework to attract potential customers, stimulate product or service interest, foster ownership desire, and ultimately drive conversion. Design/methodology/approach- This study employs a rigorous bibliometric analysis to trace temporal trends and the intellectual progression of research on the AIDA model and its link to startup success and growth. By examining publication patterns, keyword co-occurrence, and document co-citation networks, the paper quantitatively delineates the main research trajectories related to the application of the AIDA framework in new ventures. Findings-The analysis identifies key research trajectories and, crucially, pinpoints significant gaps in the current literature regarding the practical application and empirical validation of the AIDA model by startups. The synthesis reveals both the potential and the under-explored areas of the framework in dynamic, resource-constrained entrepreneurial settings. Originality/value-This paper offers one of the first bibliometric mappings of AIDA-focused research within the startup context. It provides a structured, quantitative overview that not only guides future academic inquiry but also delivers actionable insights for entrepreneurs seeking to optimize their marketing communications strategies.